CHILDREN'S DIGITAL LITERACY: PARENTAL ROLE IN PROTECTION AMID PANDEMIC AND DIGITAL SHIFT - Pranawati, Rita; Maimunah, Margaret Aliyatul; Susanto, Susanto (Universitas Negeri Yogyakarta, 2025)
The COVID-19 pandemic has brought significant changes to family life, including the role of parents in accompanying their children in the digital era. This study examines the role of parents in supporting children's digital literacy during the pandemic, while also identifying challenges in minimizing the risks of exposure to harmful online content. Using a quantitative approach, the study involved 25,164 children and 14,169 parents across Indonesia. The findings show a drastic increase in children's gadget use, with the majority of time spent on online entertainment. However, parental supervision remains limited, both in terms of quantity and quality. Only 59.1% of fathers and 68% of mothers consistently provide digital literacy education. This lack of supervision exposes children to risks such as cyberbullying, exposure to harmful content, and technology addiction. The study highlights the importance of collaboration between parents and educational institutions in strengthening safe and beneficial digital literacy practices for children in the digital era. Keywords: Children's digital literacy, family education, harmful online content, parental supervision, technology addiction.